2012
DOI: 10.1002/14651858.cd001456.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed selective surfactant treatment for neonatal respiratory distress syndrome

Abstract: Analysis 2.2. Comparison 2 Early versus delayed selective surfactant treatment in infants less than 30 weeks' gestation, Outcome 2 Mortality at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
267
5
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(296 citation statements)
references
References 48 publications
(3 reference statements)
5
267
5
6
Order By: Relevance
“…This study divulged that early administration of surfactant plays an important role in the prognosis of premature neonates with surfactant replacement therapy. This correlates with the findings of Bahadue and Soll (2012) a meta-analysis of initial hours versus late surfactant therapy concluded that the risks of mortality were significantly decreased in premature age group. This was contrary to the study conducted by Kendig et al, (1998) which showed no significant difference clinically in result between instantaneous administration of prophylactic surfactant and administration at 10 min after birth after a brief period of stabilization.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This study divulged that early administration of surfactant plays an important role in the prognosis of premature neonates with surfactant replacement therapy. This correlates with the findings of Bahadue and Soll (2012) a meta-analysis of initial hours versus late surfactant therapy concluded that the risks of mortality were significantly decreased in premature age group. This was contrary to the study conducted by Kendig et al, (1998) which showed no significant difference clinically in result between instantaneous administration of prophylactic surfactant and administration at 10 min after birth after a brief period of stabilization.…”
Section: Resultssupporting
confidence: 86%
“…This clinical report refreshes a 2008 report from the American Academy of Pediatrics (Soll, 2000). As in a report, number of clinically important topics is reviewed surrounding use of surfactant, including prophylactic versus rescue replacement, administration techniques and preparations, the synergistic effects of surfactant and antenatal steroids, and surfactant therapy for respiratory disorders other than RDS (Bahadue and Soll, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rescue surfactant treatment within two hours of life results in decrease in neonatal mortality and bronchopulmonary dysplasia. 21 Sepsis was the commonest complication in ventilated babies, as high as 67% incidence has been reported. 12 Septicemia has been reported as the commonest cause of mortality in ventilated babies.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation nowadays is to stabilize the respiration of a spontaneously breathing neonate by using CPAP and early selective surfactant administration. When an endotracheal intubation is needed due to progressive RD, the neonate should obtain surfactant as soon as possible [6,36].…”
Section: Surfactantmentioning
confidence: 99%